Business environment, economic agglomeration and job creation around the world. Issue 33 (14th July 2016) - Clarke, George; Li, Yue; Xu, Lixin Colin
ABSTRACT: This article looks at how economic agglomeration and the business environment affect job creation. The results suggest that economic agglomeration is strongly linked to job growth. Modern telecommunications, access to export markets, concentration of economic activity in large cities and capacity agglomeration, in particular, are important. In contrast, many areas of the business environment, including corruption, macroeconomic stability and infrastructure are not robustly linked to job growth. The main exception to this is that areas of the business environment directly related to labour markets are more consistently linked to job growth than other areas of the business environment.